Irrigation scheduling of tomatoes (Lycopersicon esculentum Mill.) and cucumbers (Cucumis sativus L.) grown hydroponically in coir - Van der Westhuizen, Rykie Jacoba (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD(Agric) (Agronomy))--University of Stellenbosch, 2009.